Discriminatory Treatment in Health Services for Patients Using BPJS: A Case Study of Public Services at a Private Hospital in Bogor-Indonesia - Solihin, Ihin; Kurnia, Nina (Technium Social Sciences Journal, 2022)
This study aims to answer the question of how the public’s perception of the XZ private hospital in the city of Bogor in providing services to the community using BPJS for Health, and what efforts must be made by the government so that the hospital can optimally provide services to the entire community without discrimination. This research is a qualitative research with a case study approach. Data was collected through semi-structured interviews and in a fluid atmosphere. In this study, interviews were conducted with 10 BPJS of Health users consisting of teachers, tailors, early childhood tutors, textile traders, and online taxi drivers. The researcher also interviewed 1 academician with the aim of obtaining data regarding things that must be improved in the BPJS of Health system and services. This study proves that discriminatory treatment still occurs to participants of BPJS of Health. Therefore, improving the quality of public services must be done immediately, namely by increasing the professionalism of service officers, through training programs, and simplifying the bureaucracy so that the hierarchy becomes shorter and easier for patients.